Mutations in the SARS CoV2 spike gene and their reflections on the spike protein - TURAN, KADİR (My University, 2022)
Objective: In this study, it was aimed to determine the mutation frequency in spike (S) genes of SARS CoV2 from six different regions of the world, their distribution on the gene and reflections of these mutations to the S protein. Materials and methods: SARS CoV2 S gene sequences originating from Asia, Africa, Europe, South America, Oceania and North America were obtained from NCBI virus database. The sequences were analyzed with Geneious and BioEdit multiple sequence alignment programs. Results and Conclusion: 865 distinct mutations on the S genes were detected in the virus samples. Among these, 59 variants with numbers of 10 and above in the virus population were detected. The D614G(A1841G) substitution was found to be the most common with an average of 88.6%. Furthermore, it was determined that S477N(G1430A) substitution in theviruses of Oceania differed from other regions with a rate of 86.7%. The average mutation frequency of the S genes from different regions was calculated as 4x10-5. The amino acid substitutions particularly in the RBD (receptor binding domain) have great importance for the virus adsorption to the cells via ACE2 (angiotensin converting enzyme 2) receptor and transmission. However, the importance of these mutations needs to be demonstrated both in silico and experimental studies.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Tıbbi Ekoloji ve Hidroklimatoloji; Medicine; Health Sciences; Internal Medicine Sciences; Medical Ecology and Hydroclimatology; TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); Araştırma ve Teori; İncelemeler ve Referanslar (tıbbi); Research and Theory; Reviews and References (medical); SARS CoV2; Coronavirus; Covid-19; Spike protein; Mutation; RNA VIRUS; CORONAVIRUS; PNEUMONIA; EVOLUTION